FORMULATION AND CHARACTERIZATION OF CYCLODEXTRIN BASED CURCUMIN LOADED NANOSPONGE - AKARTE, ANUP M.; PATIL, PRAKASH H. (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of proposed work is to develop and screen cyclodextrin based Nanosponge loaded with poorly soluble anticancer drug and to optimize most suitable Nanosystem with increased solubility and dissolution rate. Methods: Cyclodextrinnanosponge (CDNS) was prepared using pyromelliticdianhydride as a crosslinker for beta cyclodextrin monomer. Cyclodextrinnanosponge and curcumin were taken in 1:1 w/w proportion. The resultant curcumin loaded nanosponges were dried at 50±0.5 °C for 24 h. Results: The absorbance maxima for Curcumin was seen at 424.0 nm and for cyclodextrin was seen at 290.0 nm, The average melting point of pure drug is 181 °C which is complies with Stander melting point of drug and the aspect ratio of the nanosponge was found 1.037. Zeta potential noticed for CUR-CD-NS were more negative contrasted with separate plain CUR (−20.1±1.57) demonstrating solidness of the nanodispersion. Curcumin release from CUR-CDNS was upgraded to very nearly 10 folds toward the finish of 8 hour. Treatment with a combination of CUR-CDNS at 1:1 and 1:3 ratios resulted in an IC50 value was found 14.98 μg/ml. Conclusion: In vitro cytotoxicity study and combination index analysis showed the synergistic effect of CUR-CDNS against MCF-7 cells. The present study reveals that the combination of curcumin results in higher cytotoxicity against breast cancer cells.